2012
DOI: 10.1021/ol302443z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Nonlinearity–Transparency–Thermal Stability Trade-Off with Spirobifluorene-Bridged Donor-π-Acceptor Chromophores

Abstract: A series of novel 9,9'-spirobifluorene-bridged donor-π-acceptor chromophores containing triarylamine moieties were easily synthesized starting from the readily available reagent 4,4'-dimethylbiphenyl. These chromophores were found to combine excellent transparency in the visible region, high thermal stabilities, and large optical nonlinearity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The spirobifluorene acted as a π-conjugated bridge because of the presence of the spiroconjugation effect between the electron acceptor and the donor. [94] Compared to the values in Huang et al, [90,92] molecules with dicyanomethylene and nitrophenyl groups showed TPA cross-sections www.advopticalmat.de s of 2928 and 3773 GM, respectively. The compound with the cyano group demonstrated more than an order of magnitude increase of the TPA cross-section with s = 62 949 GM.…”
Section: Optimization Of Hyperpolarizability In Individual Moleculesmentioning
confidence: 69%
See 2 more Smart Citations
“…The spirobifluorene acted as a π-conjugated bridge because of the presence of the spiroconjugation effect between the electron acceptor and the donor. [94] Compared to the values in Huang et al, [90,92] molecules with dicyanomethylene and nitrophenyl groups showed TPA cross-sections www.advopticalmat.de s of 2928 and 3773 GM, respectively. The compound with the cyano group demonstrated more than an order of magnitude increase of the TPA cross-section with s = 62 949 GM.…”
Section: Optimization Of Hyperpolarizability In Individual Moleculesmentioning
confidence: 69%
“…The compound with the cyano group demonstrated more than an order of magnitude increase of the TPA cross-section with s = 62 949 GM. [94] These examples suggest promising strategies to improve the NLO properties of individual molecules (see Table 1 for a summary of the optical properties of the discussed molecules), yet optimal crystallization routes which would allow to obtain molecular crystals based on molecules with a spirobifluorene core yet have to be developed.…”
Section: Optimization Of Hyperpolarizability In Individual Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, a large number of chromophores have been designed with high b values and good transparency. [7][8][9][10][11] However, defeating the nonlinearity-transparency trade-off is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optical (NLO) properties of materials have been widely investigated due to potential applications in various fields such as data storage, communication and information processing [1][2][3][4]. Many organic donor-p-acceptor (D-p-A) compounds have been the focus of sizeable research efforts [5,6].…”
Section: Introductionmentioning
confidence: 99%